Celecoxib coupled to dextran via a glutamic acid linker yields a polymeric prodrug suitable for colonic delivery - Lee Y; Kim J; Kim W; Nam J; Jeong S; Lee S; Yoo JW; Kim MS; Jung Y (Dove Medical Press, 2015)
Yonghyun Lee,1,2,* Jungyun Kim,1,* Wooseong Kim,1,* Joon Nam,1,* Seongkeun Jeong,1 Sunyoung Lee,1 Jin-Wook Yoo,1 Min-Soo Kim,1 Yunjin Jung1 1College of Pharmacy, Pusan National University, Busan, 2Bio-Nanomedicine Laboratory, Department of Biological Sciences, Korea Advanced Institute of Science and Technology, Daejeon, Republic of Korea *These authors contributed equally to this work Abstract: Celecoxib, a selective cyclooxygenase-2 inhibitor, is potentially useful for the treatment of colonic diseases such as colorectal cancer and colitis. However, the cardiovascular toxicity of celecoxib limits its routine use in the clinic. Generally, colon-specific delivery of a drug both increases the therapeutic availability in the large intestine and decreases the systemic absorption of the drug, most likely resulting in enhanced therapeutic effects against colonic diseases such as colitis and reduced systemic side effects. To develop a colon-specific prodrug of celecoxib that could reduce its cardiovascular toxicity and improve its therapeutic activity, dextran–glutamic acid–celecoxib conjugate (glutam-1-yl celecoxib-dextran ester [G1CD]) was prepared and evaluated. While stable in pH 1.2 and 6.8 buffer solutions and small-intestinal contents, G1CD efficiently released celecoxib in cecal contents. Oral administration of G1CD to rats delivered a larger amount of celecoxib to the large intestine than free celecoxib. G1CD prevented the systemic absorption of celecoxib and did not decrease the serum level of 6-ketoprostaglandin F1α, an inverse indicator of cardiovascular toxicity of celecoxib. Collectively, G1CD may be a polymeric colon-specific celecoxib prodrug with therapeutic and toxicological advantages. Keywords: colon-specific drug delivery, dextran, celecoxib, prodrug, cardiovascular toxicity